A Pediatric Case of Post Traumatic Pulmonary Thromboembolism - Sibel Öz; Dinçer Yıldızdaş; Özden Özgür Horoz; Göksel Leblebisatan (Journal of Pediatric Emergency and Intensive Care Medicine, 2017)
A 10-year-old male patient with a fall-related soft tissue injury of the lateral lower left extremity was admitted to the emergency room with the complaints of flank pain, chest pain, respiratory distress and fever developing two days later. The patient was diagnosed with deep vein thrombosis and pulmonary embolism after physical examination, findings of laboratory tests, Doppler ultrasonography and computed tomography. The treatment was initiated with the infusion of tissue plasminogen activator for 6 hours, and continued with intravenous unfractionated low-molecular-weight heparin. After the respiratory distress was improved, the patient was transferred to the pediatric hematology ward. Care should be taken in these quite rare, yet highly fatal conditions known as deep vein thrombosis and pulmonary embolism in traumatized children.